Robust Hybrid LQR - Integral Control for 2-DOF Robotic Arms: Performance Evaluation under Simulated Agricultural Vibration Conditions - N. L. Quang, (EAI Endorsed Transactions on Sustainable Manufacturing and Renewable Energy, 2026)
Robotic technologies, particularly robotic manipulators, play an important role in both industrial automation and smart agriculture. In agricultural sectors where automation remains underutilized and labor cost is high, robotic solutions are necessary for enhancing productivity. However, developing agricultural robots faces significant challenges due to harsh environmental conditions, limited resources, and strict human-robot collaboration safety requirements. Consequently, advanced control algorithms are critical for maintaining high precision under operational disturbances, such as vibrations from internal combustion engine-powered tractors. This study proposes a robust Linear-Quadratic Regulator combined with Integral control (LQR-KI) for 2-DOF flexible joint robots. While flexible joint manipulators offer a safety and reduced structural weight compared to traditional rigid systems, they are affected by complex, non-ideal coupling vibrations. The proposed control structure focuses on enhancing stability and positioning accuracy, with its robustness verified through an extensive analysis of closed-loop pole trajectories under non-ideal agricultural excitations. Numerical simulations demonstrate that the LQR - KI scheme effectively isolates base vibrations, achieving a significant link positioning accuracy of 0.03 (rad). Especially, the results validate that the flexible joint configuration, optimized by the proposed controller, can achieves approximately 9.36% energy savings compared to conventional rigid-link counterparts. This research contributes to sustainable production by providing a high-performance, energy-efficient solution for integrating advanced robots into existing agricultural platforms
Keywords: Non-ideal source; LQR control; Robotic manipulators; Smart agriculture; Sustainable agriculture; Energy efficiency